2010
DOI: 10.1016/j.ejcts.2009.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of the small heat-shock protein alpha-B-crystallin in operated-on non-small-cell lung cancer patients: clinical implication☆☆☆

Abstract: Objective: Alpha-B-crystallin, a small heat-shock protein, recently gained major interest because of its differential expression during tumourigenesis and metastasis in various epithelial tumours. The purpose of this study was to investigate the expression of alpha-B-crystallin and its biologic and prognostic significance in non-small-cell lung cancer (NSCLC). Methods: Immunohistochemical analysis was performed on a tissue microarray slide containing samples from 146 NSCLC patients who were operated on between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Overexpression of αB-crystallin has been detected in a number of types of human cancer, including hepatocellular carcinoma, glioma, lung, gastric and breast cancer. The expression in cancer has been found to be correlated with lymph node metastasis, low rates of survival and poor prognosis of patients, and αB-crystallin was even considered a novel oncoprotein in basal-like breast carcinoma (11)(12)(13)(14)(15). In the current study of OVC and OSCC, we also found the overexpression of αB-crystallin.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Overexpression of αB-crystallin has been detected in a number of types of human cancer, including hepatocellular carcinoma, glioma, lung, gastric and breast cancer. The expression in cancer has been found to be correlated with lymph node metastasis, low rates of survival and poor prognosis of patients, and αB-crystallin was even considered a novel oncoprotein in basal-like breast carcinoma (11)(12)(13)(14)(15). In the current study of OVC and OSCC, we also found the overexpression of αB-crystallin.…”
Section: Discussionsupporting
confidence: 62%
“…By binding non-naive, non-host proteins or specific apoptosisrelated proteins during cellular stress, αB-crystallin protects cells from thermal shock, osmotic shock, oxidative insults, ischemia or exposure to heavy metals, and sustains cell homeostasis (9,10). αB-crystallin may play a significant role in cancer, as its overexpression has been reported in renal, hepatocellular and gastric carcinoma, glioma, and lung and breast cancers (11)(12)(13)(14). In cancer, αB-crystallin has demonstrated anti-apoptotic properties and is even considered to be a potential oncoprotein in a number of types of human cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high levels of HspB5 are associated with low survival rate in hepatocellular carcinoma (Huang et al 2013 ;Tang et al 2009 ), ovarian carcinoma (Volkmann et al 2013 ), clear cell renal cell carcinoma (Ho et al 2013 ) and head and neck squamous cell carcinoma (van de Schootbrugge et al 2013 ). In non-small-cell lung cancer only the nuclear and not the cytoplasmic localized HspB5 correlated with poor survival (Cherneva et al 2010 ).…”
Section: Hspb5 Expression In Cancersmentioning
confidence: 98%
“…The cytoplasmic expression of αB-crystallin in the tumours is related to the local invasion, while nuclear expression is more commonly detected in advanced stages, and αB-crystallin is determined as biomarker of aggressive tumour biology. They conclude that αB-crystallin plays an essential role in NSCLCs biology and its nuclear staining is an independent factor of poor survival [ 12 ].…”
mentioning
confidence: 99%
“…Cherneva et al [ 12 ] investigate the expression profile of αB-crystallin in non-small cell lung cancers (NSCLCs). In their study, cytoplasmic and nuclear expression is detected.…”
mentioning
confidence: 99%